A case of pulmonary pleomorphic carcinoma with malignant phenotypes induced by ZEB1-associated epithelial-mesenchymal transition. (2018) - Kondo, Mayo; Ogino, Hirokazu; Ogawa, Hirohisa; Afroj, Tania; Toyoda, Yuko; Sakaguchi, Satoshi; Tsuboi, Miki; Bando, Yoshimi; Goto, Hisatsugu; Tsuneyama, Koichi; Nishioka, Yasuhiko
Abstract: A 60-year-old man was admitted to our hospital with non-small cell lung cancer (NSCLC). Imaging and pathological studies revealed NSCLC, not otherwise specified (NOS), at clinical stage T3N1M0 stage IIIA. We started radiotherapy alone because of obstructive pneumonia and end-stage renal disease, but the tumors progressed rapidly and resulted in death due to air obstruction by pharyngeal metastasis. The cancer was diagnosed as pleomorphic carcinoma in an autopsy. Viable lung tumor cells, which were resistant to radiotherapy, and the pharyngeal metastasis had mesenchymal phenotypes and expressed ZEB1 but not SNAI1. These observations indicated that ZEB1-associated epithelial-mesenchymal transition has malignant features including resistance to radiotherapy and aggressive metastatic potential. ZEB1-associated EMT may be an important mechanism to understand the pathophysiology of pleomorphic carcinoma.